Breast Cancer Survivorship and Level of Institutional Involvement Utilizing Integrative Oncology. (18th December 2021) - Crudup, Terri; Li, Linna; Dorr, Jennifer Wright; Lawson, Elizabeth; Stout, Rachel; Niknam, Pedram Vazifeh; Jones, Judi; Steen, Robert G.; Casner, Susan; Lu, Lynn L.; Wang, Yi; Scott, James; et al.
Abstract : Objective . Integrative oncology is widely used by patients with breast cancer. This study aims to investigate the relationship between the survival outcomes of breast cancer patients and the level of involvement in integrative oncology at the institutions treating them. Methods . Claims-based data were used to find 4, 815 newly diagnosed breast cancer patients treated between January 2013 and December 2014 for survival analysis. A scoring system was developed by asking oncologists about their institutions' efforts to educate, support, and provide funding for 12 complementary and lifestyle approaches. Cohort analysis using two-tailed chi-square and a separate multivariate model using SMOTE and lasso regression were used. Nine variables across patient and institutional profiles were included. The model coefficients were exponentiated and presented as odds ratios. Results . 173 patients mapped to 103 institutions and 103 oncologists. The median patient age was 51, and 8% were metastatic. Institutions were scored for integrative oncology involvement and placed into four cohorts. Low-scoring institutions showed less effort to educate, support, and provide integrative therapies compared to others. The 5-year survival of patients in the low cohort was directionally but not significantly lower than others. In the multivariate model, a composite integrative oncology score was shown to increase 5-year survival odds three times for institutions in the low-mid cohort and 48% in the mid-high, compared to the low. Conclusion . Crossing the threshold beyond 'low' involvement in integrative oncology represents a new path to incremental survival benefit for many cancer patients. Entities invested in the survival of breast cancer patients should increase education, access, and funding for a core set of six therapies: nutrition counselling, exercise counselling, patient support groups, spiritual services, meditation, and psycho-oncology support.